Consumption pattern of vegetables in a child population of Pamplona: Qualitative study - Botía-Rodríguez, Irene; Cardona-Arguello, Gabriel Antonio; Carvajal-Suárez, Lennys (Universidad y Salud, 2019)
Introduction: Adequate nutrition is fundamental for the physical and intellectual development of children. Objective: To analyze the vegetable consumption pattern of a child population in Pamplona (Colombia). Materials and methods: We conducted a qualitative research with mothers that used children’s day care facilities applying the focus group discussion methodology. The information was analyzed with the Attride-Stirling tool. Results: Participating mothers considered that vegetable consumption is important and has a positive effect on children’s health. A poor consumption is caused by low quantity and frequency of supply, limited preferences for some food preparations, and inadequate examples set by parents. The purchasing frequency, place, price and organoleptic characteristics of vegetables are important factors that limit their purchase at home. Some positive and negative strategies are suggested to encourage the ingestion of vegetables in children. Conclusions: Mothers have assertive knowledge about vegetable consumption and its relation to children’s health. The level of vegetable consumption was low as it differs from the established recommendations. Praise, motivation and companionship of parents are positive strategies to encourage vegetable consumption, although some prefer punishment and reward.